Bureaucrats in business : the economics and politics of government ownership - World Bank. (Oxford ; New York : Oxford University Press, 1995)
This report shows how divestiture and other reforms can improve the economy, why politics often impede reform, and how countries that reformed successfully overcame these obstacles.
"Published for the World Bank."
Includes bibliographical references (p. 325-340) and index.
oif 02/11/15
Loan
Keywords: Government ownership; Government business enterprises; Industrial efficiency; Socialism; Developing countries